Andra Ursuţa: Alps - Bell, Natalie 1967-; Gioni, Massimiliano 1973- (New Museum, 2016)
Combining formal innovation with dark humor and social commentary, the work of Romanian-born artist 'Andra Ursuta' (born 1979) uses parody and blasphemy to expose power dynamics, probe the vulnerability of the human body and examine modes of desire. Ursuta's sculptures and installations engage a visual language that weaves an art-historical homage with a homespun, anarchic sensibility. Ursuta has lived in the US since the late 1990s, but many of the facets of her upbringing--from occult folk traditions to nationalist propaganda--resonate throughout her work. This volume, the artist's first catalogue, marks her 2016 solo exhibition at the New Museum. It features an interview between Ursuta and Massimiliano Gioni, a new essay by Natalie Bell and a sardonic aesthetic prescription by artist Maurizio Cattelan. Exhibition: The New Museum, NYC, USA (27.04.-19.06.2016)